(untitled) (Homoeopathy for All, 2025)
Cholelithiasis is primarily consider as a surgical disease by modern medicine which can be readily manageable and curable with Homoeopathic medicine, as Homoeopathy treats not only the disease entity but also the patient as a whole. With Homoeopathic intervention surgery is not necessary in Cholelithiasis and thus Gall bladder was preserved and reverted back to its normal functioning. In the present study after giving constitutional remedy to every patient according to law of Similia in Homoeopathy. The drugs were given for the period of 3 to 5 month as per need, the patient responded well to our treatment and wonderful results were found in recovery rate. It proves the efficacy of constitutional medicine in Cholelithiasis.